ISLAMISM AND ISLAMIZATION: MUSLIM ENCOUNTER WITH HINDUS IN THE INDIAN SUBCONTINENT - Singh, David Emmanuel (Journal of Dharma, 1999)
The Muslim psyche experienced unprecedented stir beginning from the 19th century when European colonization began to facilitate the birth of new ideas of secularism, democracy and nationalism. Traditional Muslim intellectuals have understood secularism to involve separation of the state from the divine realm. Democracy to them, has involved rule of the majority based on human constitutions in place of the revelation of God contained in scriptures and nationalism has been viewed as worship of the territory in place of one sovereign God. The ideas of secularism and democracy not only made space of plurality of laws and nations but also created space for religious entities. Muslim intellectuals like Hasan al-Banna, Sayyid Qutb, Iqbal, Mawdudi and others responded to the problem and challenge of plurality, western secularism and democracy bred, by formulating their integrative political ideology based on the idea of One sovereign God-one law). Such a response has also been called 'Islamism